1991
DOI: 10.1007/bf00197799
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin perception at the plasma membrane of Avena fatua aleurone protoplasts

Abstract: A functional assay for gibberellin (GA) receptors is described based on the induction of α-amylase gene expression in isolated aleurone protoplasts of Avena fatua L. by GA4 immobilised to Sepharose beads. A 17-thiol derivative of GA4, shown to be biologically active with aleurone protoplasts, has been coupled to epoxy-activated Sepharose 6B. This GA4-17-Sepharose induces high levels of α-amylase when incubated with isolated aleurone protoplasts, while cells of the intact aleurone layer do not respond appreciab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(88 citation statements)
references
References 25 publications
0
88
0
Order By: Relevance
“…The Ca2+-dependent and Ca2+-independent signal transduction pathways from ABA may well originate from independent receptor systems. It was previously observed that only ABA presented to the extracellular face of the aleurone protoplast is effective at inhibiting a-amylase secretion (Hooley et al, 1991;Gilroy and Jones, 1994). However, preliminary experiments using microinjection of ABA suggest that intracellular ABA is active in triggering the induction of Em-GUS, suggesting an intracellular receptor (S. Gilroy, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ca2+-dependent and Ca2+-independent signal transduction pathways from ABA may well originate from independent receptor systems. It was previously observed that only ABA presented to the extracellular face of the aleurone protoplast is effective at inhibiting a-amylase secretion (Hooley et al, 1991;Gilroy and Jones, 1994). However, preliminary experiments using microinjection of ABA suggest that intracellular ABA is active in triggering the induction of Em-GUS, suggesting an intracellular receptor (S. Gilroy, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ultrastructural changes in the secretory apparatus that accompany GA stimulation have been determined (Hillmer et al, 1990). However, although the site of perception of GA and ABA is now tentatively assigned to the aleurone cell plasma membrane (Hooley et al, 1991;Gilroy and Jones, 1994), the GA and ABA perception systems and the subsequent signal transduction events remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of other GA receptors and signaling pathways, perhaps specific to particular developmental processes, cannot be discounted. Indeed, there is considerable, albeit indirect, evidence for the existence of membrane-associated receptors for GA, most notably in the cereal aleurone (Hooley et al, 1991;Gilroy and Jones, 1994;Lovegrove and Hooley, 2000).…”
Section: The Gid1 Triple Mutant Displays Severe Growth Defectsmentioning
confidence: 99%
“…These enzymes act on storage macromolecules producing nutrients for the embryo. GA covalently bound to sepharose beads induces the expression of a-amylase genes in oat aleurone protoplasts but not in cells with an intact wall (Hooley et al, 1991). These results, along with additional control experiments, suggest that the response is not due to the release of GA from the sepharose.…”
Section: Do Plants Have Additional Ga Receptors?mentioning
confidence: 68%